Criminal Law Policy on Drug Abuse from a Health Perspective - Mhd. Ihwanuddin Hasibuan; Helviana Hasibuan; Yasmirah Mandasari Saragih (International Forum of Researchers and Lecturers, 2026)
Drug abuse in Indonesia has reached an alarming level and has become a complex legal and health problem. This study aims to examine the criminal law policy applied to drug abusers from a health perspective, with a focus on the rehabilitative approach as an alternative to punishment. The method used is normative legal research with a statute approach and a conceptual approach, through a literature study of laws and regulations, court decisions, and relevant scientific literature. The results of the study indicate that Law Number 35 of 2009 concerning Narcotics contains a dualistic approach, namely punishment (penal) and rehabilitation (non-penal), but its implementation still tends towards imprisonment. From a health perspective, drug abuse is an addictive disorder that requires a medical and psychosocial approach, not solely a criminal repressive approach. An ideal criminal law policy should combine proportional criminal sanctions with a comprehensive medical and social rehabilitation program. This study recommends policy reforms that are more oriented towards the health recovery of drug abusers without neglecting the aspect of law enforcement against drug dealers and traffickers.